Indeks massa tubuh dan aktivitas fisik dengan tekanan darah pada pelajar SMA - Yessi Marlina; Emy Huryati; Yati Soenarto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: A trend towards in increase of hypertension in adults and children. If criteria of hypertension according to JNC VII 2003 applied to the population aged 15-17 years in Indonesia, the prevalence of hypertension in adolescents was obtained 5.3% nationally. Examination of blood pressure and factors related to blood pressure are of particular importance in children due to the decline in physical activity and weight changes contributing to blood pressure elevations that occur at this point in maturation. Blood pressure levels begin to increase as children approach adolescence. Weight control and physical activity regularly are recommended to prevent blood pressure elevations in both adult and youth.Objective: Determine the relationship between body mass index and physical activity with blood pressure in high school students in Pekanbaru.Method: This is an analytic observational study with cross sectional design. This study was involved 353 high school students in Pekanbaru who meets inclusion and exclusion criteria through cluster sampling technique. Data collected by direct measurements such as weight, height and blood pressure whereas physical activity and characteristic of the subject was collected by questionnaire. The results of the data collection were analyzed using univariate, bivariate and multivariate analysis.Results: There is a correlation between body mass index with systolic (p=0.000; r=0.238) and diastolic blood pressure (p=0.010; r=0.136). Each increase in 1 kg/m2 body mass index was linked with an increase of 2.339 mmHg systolic blood pressure and 0.979 mmHg diastolic blood pressure. However, there is no correlation between physical activity with systolic (p=0.829) nor diastolic blood pressure (p=0,643). Multivariate analysis showed that sex and screen time activity were factors most dominantly affecting blood pressure.Conclusion: There is a correlation between body mass index with blood pressure. However, there is no correlation between physical activity with blood pressure.